SPE Annual Technical Conference and Exhibition 2007
DOI: 10.2118/110638-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Manganese Tetra-Oxide/KCl Water-Based Drill-in Fluids for HT/HP Wells

Abstract: Drilling Unayzah-B gas reservoir (shale and sandstone) in Saudi Arabia requires high mud density (± 95 pcf). To formulate this mud, calcium carbonate particles were used, because of their high acid solubility. However, when drilling the 5–7/8 inch hole, sticking occurred, which resulted in expensive fishing and/or sidetrack operations. To minimize these problems, barite was added with CaCO3 to reduce the amount of solids needed to formulate the drill-in fluid. However, barite is acid in-soluble and may cause f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The producing wells were perforated with small charges resulting in small holes long enough to pass any damage in the near-wellbore region. Recently, Al-Yami et al (2007 designed water-based drill-in fluids using Mn 3 O 4 . Their work showed that several polymers can be used to design KCl/Mn 3 O 4 drillin fluids.…”
Section: Water-based Mn 3 O 4 Drill-in Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The producing wells were perforated with small charges resulting in small holes long enough to pass any damage in the near-wellbore region. Recently, Al-Yami et al (2007 designed water-based drill-in fluids using Mn 3 O 4 . Their work showed that several polymers can be used to design KCl/Mn 3 O 4 drillin fluids.…”
Section: Water-based Mn 3 O 4 Drill-in Fluidsmentioning
confidence: 99%
“…Formate drill-in fluids with low solids content can be used, but they are expensive and corrosive at pH values less than 7-8. A third drilling fluid was developed recently by Al-Yami et al (2007) to overcome some of the problems associated with these two systems.The objectives of this study are to determine solids invasion and damage characteristics for the three fluids. Coreflood tests were conducted using reservoir cores at bottomhole conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the suitable combination of these components can efficiently provide physical stability, cuttings transport, lubricity, and overall formation damage control (Al Yami 2007;Al-Saeedi et al 2010;Al Moajil et al 2011;Kho et. It has been shown that the suitable combination of these components can efficiently provide physical stability, cuttings transport, lubricity, and overall formation damage control (Al Yami 2007;Al-Saeedi et al 2010;Al Moajil et al 2011;Kho et.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese tetra-oxide (Mn 3 O 4 ) is another weighting material that has slightly better solubility than barite, but it still can lead to formation damage. 22 High-density brines offer a viable option for reducing the problems encountered by high solids loading. However, the choice of polymers is critical due to solubility limitations and yielding of the desired viscosity response and fluid loss control.…”
Section: Introductionmentioning
confidence: 99%